Information management in the sharing economy - Chua, Alton Yeow Kuan (2023)
The objective of this paper is to present a research agenda for information management in the sharing economy. Drawing from a total of 591 full-length articles in Scopus database published between 2012 and 2021, VOSViewer was used to identify significant keywords in existing sharing economy research as well as collaboration patterns across individuals, institutions and countries. The results show four groups of keyword co-occurrences, and three groups of highly connected authors, universities and countries. Together, they not only offer research directions in which interested scholars can pursue but also highlight various collaboration opportunities.